Does Turnover Inhibit Specialization? Evidence from a Skill Survey in Peru - Andrea Atencio-De-Leon; Munseob Lee; Claudia Macaluso (Center for Economic Studies and ifo Institute (CESifo), 2023)
We design, pilot, and field a new survey of occupational skills in Peru, to investigate human capital differences between poor and rich countries. Though the average skill level is comparable, Peruvian jobs have markedly more uniform skill profiles than jobs in the US. However, matching frictions are no more severe than in the US, and recruiting technology is largely equivalent as well. A model with complementarities in production offers a plausible explanation. Uncertainty about labor availability, more pronounced in poor countries' turbulent labor markets, destabilizes production. This generates an endogenous labor demand preference for unspecialized workers.
Keywords: E24; O11; O47; 330; cross-country productivity differences; human capital; labor reallocation